Effect of impaired glycosylation on the biosynthesis of Semliki forest virus glycoproteins. - Kaluza, G (1975)
The glycoproteins of Semliki Forest virus, grown in chicken embryo cells, were labeled with radioactive sugars. The data indicate a high mannose content of the nonstructural precursor glycoprotein NSP 63. This protein can also be readily labeled with 2-deoxy-D-glucose. The envelope glycoproteins E1 and E2 are relatively rich in galactose, glucosamine, and fucose. Glycosylation can be impaired by 2-deoxy-D-glucose or D-glucosamine or by omission of sugars in the culture medium. Under these conditions characteristic changes in the electrophoretic profile of the viral polypeptides are observed: in the regions of glycoproteins NSP 97, NSP 63, and E1 and E2 new protein peaks can be detected. These polypeptides seem to be aberrant forms of the glycoproteins. When compared with the normal molecules they have lower molecular weights and contain less carbohydrates, especially mannose. Pulse-chase experiments indicate that the altered glycoproteins are degraded very slowly if at all. If, however, impairment is caused by omission of sugars in the culture medium, the radioactivity is chased after addition of glucose from the region between NSP 63 and E1 + E2 into the E1 + E2 peak. This suggests a completion of the carbohydrate chains under these conditions.